IMPLEMENTATION OF KNOWLEDGE SHARING PROGRAM AT YAYASAN TABU INDONESIA BERDAYA - Alam, Rohmat; Winoto, Yunus; Koswara, Iwan (Jurnal Ilmiah Multidisiplin, 2024)
Tabu.id is a foundation-based community that actively practices knowledge sharing. Since 2017, Tabu.id has focused on advocating for the rights of Indonesian youth in the field of sexual and reproductive health and related education. This research aims to evaluate and improve the efficiency of knowledge sharing. The focus of this research is to describe the knowledge sharing process, known as socialization, that occurs at Yayasan Tabu Indonesia using the SECI model. Using a qualitative case study approach, the data were collected through observation, interviews, and literature review. Yayasan Tabu Indonesia Berdaya (Tabu.id) implements a knowledge sharing strategy among its members as part of a community development effort aimed at creating knowledge about comprehensive sexuality education. The knowledge sharing methods employed by Tabu.id encompass various activities and factors that contribute to the success of knowledge sharing. These activities include coordination meetings, informal discussions, and SRHR & SBCC training. During these sessions, members exchange knowledge and experiences, resulting in new insights for other members. The primary factor driving the success of knowledge sharing activities at Tabu.id is the collective awareness of the importance of managing comprehensive sexuality education knowledge, given Indonesia's significant need for this information.